A genomic approach for the identification of population management units for the dolphinfish (Coryphaena hippurus) in the eastern Pacific - Mar-Silva, Adan Fernando; Díaz-Jaimes, Píndaro; Ochoa-Zavala, Maried; Ortega-Garcia, Sofia; Sotil, Giovanna; Alegre, Ana; Escarabay, Teddy; Elias, Esteban; Carvajal-Rodríguez, Jose Miguel (Frontiers in Marine Science, 2024)
In the Tropical Eastern Pacific dolphinfish (TEP) Corypahena hippurus is part of commercial, recreational, and artisanal fisheries and is also caught incidentally by the tuna purse-seine and longline fisheries. Defining the existence of differenced populations in exploited species for being considered independent management units is crucial for conservation plans. However, there is a great uncertainty about the species population genetic structure across the TEP. To investigate it and to identify possible management units for conservation purposes this study was carried out, based on two SNPs datasets of 3867 and 3220 SNPs for young of the year (YOY) and adult individuals, respectively, obtained through NGS protocols. Sampling covered the species’ range distribution in the Tropical Eastern Pacific and was structured into YOY and adult individuals in order to discard the effects of migrating individuals into sampled locations. Our results revealed slight but significant differences among locations occupying the latitudinal limits of the species distribution at transitional areas between tropical and subtropical waters. These areas are characterized by strong seasonal variations in sea surface temperature and limit the prevalence of populations in these extremes. Genetic differences also seem to be related to spatial separation of locations as the northernmost (Los Cabos) and southernmost (Peru) locations including a set of oceanic samples, showed the highest levels of genetic differentiation. Whereas were detected barriers to gene flow among spatially separated locations for YOY individuals probably related to site fidelity, clear limitations to gene flow between Mexico and Central America locations were observed probably related to oceanic circulation in the area. Design management strategies in countries where the dolphinfish is explored is of primary interest to preserve genetic resources. It is necessary to define the existence of genetic differences of populations for species that are highly dependent on environmental factors limiting its distributional range as is the case of the dolphinfish.